Enhancing the oxygen evolution reaction activity of CuCo based hydroxides with V2CTx MXene - Koutsioukis, Apostolos; Nicolosi, Valeria; Douglas-Henry, Danielle (My University, 2024)
The oxygen evolution reaction (OER) is a key reaction in the production of green hydrogen by water electrolysis. In alkaline media, the current state of the art catalysts used for the OER are based on non- noble metal oxides. However, despite their huge potential as OER catalysts, these materials exhibit various disadvantages including lack of stability and conductivity that hinder the wide-spread utilization of these materials in alkaline electrolyzer devices. This study highlights the innovative chemical functionalization of a mixed copper cobalt hydroxide with the V2CTx MXene to enhance the OER efficiency, addressing the need for effective electrocatalytic interfaces for sustainable hydrogen production. The herein synthesized CuCo@V2CTx electrocatalysts demonstrate remarkable activity, outperforming the pure CuCo catalysts for the OER and moreover show increased efficiency after 12 hours of continuous operation. This strategic integration improved the water oxidation performance of the pure oxide material by improving the composite's hydrophilicity, charge transfer properties and ability to hinder Cu leaching. The materials were characterized using an array of materials characterization techniques to help decipher both structure of the composite materials after synthesis and to elucidate the reasoning for the OER enhancement for the composites. This work demonstrates the significant potential of TMO-based nanomaterials combined with V 2CTx for advanced innovative electrocatalytic interfaces in energy conversion applications.
PUBLISHED